THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING PRACTICE AND THE PHENOMENON OF WASTING (MALNUTRITION) AND STUNTING IN LERAN VILLAGE, BOJONEGORO, INDONESIA - Naini, Sofi Maziatus; Fadilah, Aini; Y, Berliana Farah; Arini , Shintia Yunita (International Journal of Psychosocial Rehabilitation, 2020)
Exclusive breast milk is very important for children’s growth and development. So, the effects that can occur if the mothers do not breastfeed the children with exclusive breast milk are wasting and stunting. This study aimed to know the relationship between the phenomenon of wasting and stunting and exclusive breastfeeding practice in Leran village. The research method used was an observational study with a cross-sectional approach. The total sample of 63 children under five was taken using simple random sampling. The data related to exclusive breastfeeding practice were collected using questionnaires, while the data of stunting and wasting in children under five were collected from the anthropometric measurements. The result of this study was 9.5% of children under five were wasted, 39.7% of children under five were stunted, and 96.8% of children under five were breastfed with exclusive breast milk. This study concludes that there is no relationship between exclusive breastfeeding practice and stunting. Meanwhile, there is a relationship between exclusive breastfeeding practice and wasting.